Preliminary estimation of infantile exposure to BPA based on the standard quality of baby bottles distributed in Isfahan urban society - Zohreh Abdi Moghadam; Hamidreza Pourzamani; Akbar Malekpour; Maryam Mirlohi; Zohreh Amininoor (International Journal of Environmental Health Engineering, 2013)
Aims: This study was aimed to estimate the bisphenol A (BPA) intake from baby bottles, considering the diversity and the standard quality of the baby bottles distributed in an Isfahan urban society. Materials and Methods: A cross-sectional study was performed in Isfahan in 2011. Baby shops ( n = 33) and drug stores ( n = 7) in four district areas were included in the study. The distribution of baby bottles was investigated regarding their brand, origin, and being labeled "BPA free." Estimation of exposure to BPA from baby bottles was made based on the national and international representative data. Results: The products marked as "BPA free" were found among the western products and limited to two of the selected areas. No "BPA free" marked baby bottle was distinguished among the Iranian made products. Of the 8% exclusively formula-fed infants, 90% may be the high consumers of BPA from polycarbonate baby bottles, with an intake of 1.5-2 μg/kg b.w./day for the moderate and 7.5-10 μg/kg b.w./day in case of worse condition. Conclusion: Considering the current globally accepted threshold daily intake (TDI) for BPA, primary exposure estimation is that feeding using non-BPA-free baby bottles is not a serious health concern in Iran. Thought that threshold level of TDI is discussed to be reduced in future, improvement and revision of the national standards can be effective in reducing the exposure to BPA in Iranian infants so as to provide large margin of safety for them.